1960
DOI: 10.1017/s0022029900010128
|View full text |Cite
|
Sign up to set email alerts
|

Chemical changes in dried skim-milk during storage

Abstract: Dried skim-milk stored at 55 °C in air at 70 % relative humidity has been found to contain lactulose, galactose, tagatose, glyceraldehyde and maltol; and formic, acetic and glycollic acids. These compounds are not present, or are present only in trace quantities, in fresh dried skim-milk. It is suggested that while the proteinsugar reaction is responsible for most of the browning of the powder, many of the compounds found are formed by degradation of lactose catalysed by the free basic amino groups of the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1965
1965
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Tagatose is a ketose (stereoisomer of D-fructose) which occurs naturally in various foods, such as sterilized and powdered cow's milk, hot cocoa, a variety of cheeses, yogurt and other dairy products. [34][35][36][37] Moreover, people have been chronically exposed to tagatose through use of two common drugs, Chronulac® and Cephulac®. 38 Since the tagatose was first described, 34 the attractiveness of this compound has grown dramatically attracting the commercial trademark of Naturlose™ §.…”
Section: Introductionmentioning
confidence: 99%
“…Tagatose is a ketose (stereoisomer of D-fructose) which occurs naturally in various foods, such as sterilized and powdered cow's milk, hot cocoa, a variety of cheeses, yogurt and other dairy products. [34][35][36][37] Moreover, people have been chronically exposed to tagatose through use of two common drugs, Chronulac® and Cephulac®. 38 Since the tagatose was first described, 34 the attractiveness of this compound has grown dramatically attracting the commercial trademark of Naturlose™ §.…”
Section: Introductionmentioning
confidence: 99%
“…This proposed mechanism appears unlikely owing to the high stability of lactulosyl-lysine although lysine is now known to constitute the N-terminal group of a s2 -casein. Richards & Chandrasekhara (1960) suggested that the reaction was probably base catalysed as the rate of epimerization increases with increasing pH. It was therefore suggested that the available amino groups of casein acted as a base and abstracted a proton from lactose which then rearranged to form lactulose.…”
mentioning
confidence: 99%
“…D‐tagatose occurs naturally in Sterculia setigera gum, and it is also found in small quantities in various processed foods such as sterilized and powdered cow's milk, hot cocoa, and a variety of cheeses, yogurts, and other dairy products (Richards and Chandrasekhara 1960; Troyono and others 1992; Mendoza and others 2005). D‐tagatose can be produced from D‐galactose by a chemical method using a calcium catalyst (Beadle and others 1991), but the process has some disadvantages, such as complex purification steps, chemical waste formation, and by‐products formation.…”
Section: Tagatosementioning
confidence: 99%